2019
DOI: 10.1002/jcop.22160
|View full text |Cite
|
Sign up to set email alerts
|

The role of parenting stress in mediating the relationship between neighborhood social cohesion and depression and anxiety among mothers of young children in fragile families

Abstract: This study was designed to examine the roles of neighborhood social cohesion and parenting stress in influencing maternal mental health outcomes among primarily low‐income, unmarried, urban mothers. Structural equation modeling was conducted using cross‐sectional Fragile Families and Child Wellbeing Study data (N = 3,876), to test the hypotheses that neighborhood social cohesion would be associated with depression and anxiety among mothers with children aged 3 years and that this relationship would be mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 54 publications
3
29
0
Order By: Relevance
“…The potential impact of stress on anxiety, depression, and other neuropsychiatric disorders is well-documented [9,10] often, following disasters, resulting in posttraumatic stress disorder (PTSD) and substance use disorders [11]. Moreover, since the same preventive measures meant to limit the spread of an infection can paradoxically also heighten risks due to increased social conflict, isolation, devaluation, rejection, and exclusion, such efforts may be somewhat counterproductive [12].…”
Section: Introductionmentioning
confidence: 99%
“…The potential impact of stress on anxiety, depression, and other neuropsychiatric disorders is well-documented [9,10] often, following disasters, resulting in posttraumatic stress disorder (PTSD) and substance use disorders [11]. Moreover, since the same preventive measures meant to limit the spread of an infection can paradoxically also heighten risks due to increased social conflict, isolation, devaluation, rejection, and exclusion, such efforts may be somewhat counterproductive [12].…”
Section: Introductionmentioning
confidence: 99%
“…The potential impact of stress on anxiety, depression, and other neuropsychiatric disorders is well-documented[9,10] – often, following disasters, resulting in post-traumatic stress disorder (PTSD) and substance use disorders[11], Moreover, since the same preventive measures meant to limit the spread of an infection can paradoxically also heighten risks due to increased social conflict, isolation, devaluation, rejection, and exclusion, such efforts may be somewhat counterproductive[12], These effects of increased, sustained psychological stress on individuals who, for various reasons, may be differentially impacted should not be discounted.…”
Section: Introductionmentioning
confidence: 99%
“…McCloskey and Pei [ 19 ] found that NSC relationship has an impact on maternal mental health and that efforts to strengthen neighborhood social cohesion may improve outcomes by reducing childcare stress. Furthermore, Chen et al [ 18 ] showed that social relationship capital influences PA for those aged 15 to 69 years, noting that social participation expands the social network of residents and positively influences PA and nutrition.…”
Section: Methodsmentioning
confidence: 99%
“…At the interpersonal level, evidence suggests that parental lifestyle is significantly associated with children’s PA and ST [ 14 , 15 , 16 , 17 ]. Additionally, growing evidence has shown that neighborhood social capital (NSC), which is defined as the resources accessed by individuals as a result of their membership of a network or a group, is associated with parental lifestyle [ 18 , 19 ], which in turn influences children’s SH.…”
Section: Introductionmentioning
confidence: 99%